Exploring the Use of Instructional Media in English Teaching at SMAN 1 Kalukku: Challenges and Opportunities in EFL Classrooms - Hamdi Nur, Rapi (Jurnal Ilmiah Multidisiplin Amsir, 2025)
This study aims to explore the use of instructional media in English teaching at SMAN 1 Kalukku, focusing on the challenges and opportunities encountered in EFL classrooms. This research employed a qualitative approach with a case study design to obtain an in-depth understanding of teaching practices. The population of this study consisted of all English teachers and students at SMAN 1 Kalukku. The sample included 2 English teachers and 28 students, selected through purposive sampling to represent active participation in classroom learning. Data were collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that teachers utilized various types of instructional media, including audiovisual media, digital platforms, and printed materials, to support the teaching and learning process. The use of instructional media contributed positively to students’ engagement, motivation, and comprehension of learning materials. However, several challenges were identified, such as limited technological facilities, inconsistent internet access, and varying levels of teachers’ digital literacy. Despite these constraints, the study also found opportunities in the integration of media, particularly in fostering interactive learning environments and enhancing students’ language skills. In conclusion, the effective use of instructional media plays a significant role in improving English teaching practices in EFL classrooms. Therefore, it is recommended that schools provide adequate technological support and training for teachers to maximize the benefits of instructional media in language learning.